Pengaruh Voluntary Disclosure of Financial Information dan CSR Disclosure terhadap Earning Response Coefficient - Hesti Fitriani; Erna Setiany (Jurnal Akuntansi dan Bisnis, 2014)
The purpose of this study is to determine the effect of voluntary disclosure of financial information and CSR disclosure to earning response coefficient on manufacturing companies listed in Indonesian Stock Exchange in 2010-2012. This study use disclosure index proposed by Setiany (2013) to measure the scope of the voluntary disclosure of financial information. As for the CSR Index, adapted from Sembiring (2005), which measures the scope of CSR disclosure. Earnings response coefficient is measured by cumulative abnormal return regression (CAR) with unexpected earnings (EU) ± 5 (five) days in the period from the date of issuance window annual report. This study uses multiple regression analysis. Samples of this research are 75 companies listed on Indonesia Stock Exchange in 2010-2012. The results indicated that voluntary disclosure of financial information have no significant effect on earnings response coefficient, while CSR disclosure has a positive effect on earnings response coefficients